2015
DOI: 10.3989/scimar.04219.05a
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the pearly razorfish, <em>Xyrichtys novacula</em> (Actinopterygii: Labridae), in sand-seagrass mosaics: spatial variation according to habitat features and sampling techniques

Abstract: Summary:Habitat structure affects the distribution of fishes, particularly across reef-dominated habitats, but few studies have connected patterns in the abundance of soft-bottom fishes with the structure of the habitat. The spatial and temporal patterns of variation in the abundance, biomass and population structure of the pearly razorfish, Xyrichtys novacula, inhabiting sand-Cymodocea nodosa seagrass mosaics were described through two complementary techniques: underwater visual counts and seine nets. We soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Marconato et al (1995) and Shen and Clark (2016) described the haremlike social structure of this species, where males were observed encompassing the smaller sub-territories of two to six females. The male:female proportion of individuals included in the study (1:1.93) was similar to the ratio described for this species using underwater visual censuses (1:85, Espino et al, 2015), but higher than the ratio obtained by the same authors using trawls (1:4.9). This suggests that males could be overrepresented in our dataset, probably because they are more susceptible to be fished due to their territorial behavior.…”
Section: Figure 5 |supporting
confidence: 83%
“…Marconato et al (1995) and Shen and Clark (2016) described the haremlike social structure of this species, where males were observed encompassing the smaller sub-territories of two to six females. The male:female proportion of individuals included in the study (1:1.93) was similar to the ratio described for this species using underwater visual censuses (1:85, Espino et al, 2015), but higher than the ratio obtained by the same authors using trawls (1:4.9). This suggests that males could be overrepresented in our dataset, probably because they are more susceptible to be fished due to their territorial behavior.…”
Section: Figure 5 |supporting
confidence: 83%
“…In general, it has been found that aggressiveness plays an important role in social structure, where the most aggressive males have a higher position in the mating hierarchy ( McGhee & Travis, 2010 ). This could be the case of the pearly razorfish, a species that lives in harems formed by a male and several females ( Espino et al, 2015 ) and where there is intra-sexual but not inter-sexual competition. Male and female territories usually overlap, suggesting that the shared space is used for reproduction ( Shen & Clark, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been found that aggressiveness plays an important role in social structure, where the most aggressive males have a higher position in the mating hierarchy (McGhee & Travis, 2010). This could be the case of the pearly razorfish, a species that lives in harems formed by a male and several females (Espino et al, 2015) and where there is intrasexual but not between-sexes competition. Male and female territories usually overlap, suggesting that the shared space is used for reproduction (Shen & Clark, 2016).…”
Section: Discussionmentioning
confidence: 99%